Type 2 diabetes remission through lifestyle intervention in a geriatric patient with long-standing diabetes and at thirty-three-months follow-up - Pramod Tripathi; Diptika Tiwari; Milanjeet Kaur Raizada; Nidhi Kadam (Endocrinology, Diabetes & Metabolism Case Reports)
Type 2 diabetes (T2D) is a chronic metabolic disorder that affects millions of people worldwide, particularly the elderly population. Remission of T2D in elderly patients through lifestyle modifications has been well documented, especially in newly diagnosed patients with good glycemic control and without obesity. It is also common in patients with obesity undergoing bariatric surgery. In this report, we present the case of a 66-year-old male patient with a 30-year history of T2D and mild obesity who achieved remission of T2D through customized integrated intensive lifestyle modifications, including a vegan diet, exercise and psychological support. The patient showed an improvement in HbA1c (7.7 to 5.3%) and insulin resistance (HOMA-IR; 6.2 to 1.8) and a shift in BMI (25.3 to 23.7 kg/m2) through weight loss (73 to 67 kg). The patient remains in remission 33 months after the completion of the intervention. This case suggests the possibility of long-term remission with lifestyle changes in patients with advanced age, a longer duration of diabetes and mild obesity.